Promoting the Calcium-Uptake Bioactivity of Casein Phosphopeptides in vitro and in vivo - Liu, Guo; Guo, Baoyan; Sun, Shengwei; Luo, Minna; Liu, Fei; Miao, Jianyin; Tang, Jian; Huang, Yahui; Cao, Yong; Song, Mingyue (Frontiers in Nutrition, 2021)
Casein phosphopeptides (CPP) have been studied widely for their ability to chelate calcium. However, systematic studies on the effects of CPP on calcium absorption in vitro and in vivo were scarce. Here, in vitro calcium binding capacity of CPP2 was 142.56 ± 7.39 mg/g, which was higher than that of CPP1 (107.15 ± 6.27 mg/g). Calcium transport results in a Caco-2 monolayer model indicated that relative to controls, CPP1 and CPP2 increased calcium transport by 21.78% and 53.68%, respectively. Subsequent animal experiments showed that the CPP2-Ca-H group (1% Ca, 0.4% CPP2) had a significant increase in the femur index, serum Ca2+ and serum osteocalcin levels, and femoral Ca content. CPP2-Ca-H animals also had decreased serum alkaline phosphatase levels, parathyroid hormone content and urinary pyridinoline content. Overall, our results demonstrated that CPP2 had stronger effects on promoting calcium uptake than CPP1.